The Effectiveness of Using Smart Box Media on the Learning Motivation of Eighth Grade Students in Pancasila Education at SMPN 5 Banyuwangi - Rizki Wardani Putri; Desi Yunita Putri; Andika Ronggo Gumuruh (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Learning motivation determines students' engagement in Pancasila Education, yet lecture- and textbook-based learning may reduce participation. This study examined the effectiveness of Smart Box learning media in improving the learning motivation of eighth-grade students at SMPN 5 Banyuwangi. A quantitative quasi-experimental method with a nonequivalent control group design was used. The participants were 67 students: 34 in the experimental class and 33 in the control class. Data were collected through observation, a learning motivation questionnaire, and documentation, then analyzed using descriptive statistics, Shapiro-Wilk normality tests, Levene homogeneity tests, and an Independent Sample t-Test. The experimental class mean increased from 66.29 to 86.59, while the control class mean increased from 73.52 to 83.88. The posttest result was significant (p = 0.021 < 0.05). Thus, Smart Box media effectively improved learning motivation by making learning more concrete, interactive, and participatory.